The eye's mind: Bridget Riley collected writings 1965-2019 - Riley, Bridget 1931- (The Bridget Riley Art Foundation, 2019)
Bridget Riley, one of the leading abstract painters of her generation, holds a unique position in contemporary art. She has developed and extended the range of her interests ever since her first success in the 1960s, creating a body of work which is both consistent and highly varied. This volume, now fully revised and updated, reveals the mind behind this remarkable aachievement, drawing together the most important texts and interviews of the last fifty years. Riley's writings show a passionate engagement with her subjects and a great insight paired with a freshness of approach and an exceptional clarity of expression. Quite apart from providing a key to understanding her own work, this book is a fascinating document reflecting the issues and problems facing an artist in the 21st century
Keywords: Riley, Bridget -- 1931-; Geschichte 1965-2019; Abstrakte Malerei; Theorie; Aufsatzsammlung; Interview